Study on toughness improvement of a rosin-sourced epoxy matrix composite for green aerospace application - Hu, Dongyuan; Zhang, Xvfeng; Liu, Xiaoling; Qin, Zhen; Hu, Li; Rudd, Chris; Yi, XiaoSu (MDPI AG, 2020)
A high temperature epoxy resin was formulated by using a rosin-sourced anhydride-type curing agent, i.e., maleopimaric acid (RAM), and a two-component epoxy consisting of an E51-type epoxy and a solid phenolic epoxy to form a bio-sourced green matrix resin. The glass transition temperature of the final resin was 238◦C Carbon fiber composite prepreg and was manufactured and laminated into composite specimens. Interleaving Toughening Technology (ITT) was applied to the laminates by using Polyamide interleaf veils. The interlaminar fracture toughness and compression after impact (CAI) strength were investigated and showed that the opening Mode I interlaminar fracture toughness GIC and the Mode II interlaminar fracture toughness GIIC of the specimens with interleaves were significantly improved from 227.51 J/m2 to 509.22 J/m2 and 1064.3 J/m2 to 1510.8 J/m2, respectively. Correspondingly, the drop-weight impact test shows that the interleaves reduced the impact damage area from 20.9% to 11.3% of the total area, and the CAI residual strength was increased from 144 MPa to 191 MPa. Meanwhile, mechanical tests showed that the in-plane properties of the interleaved laminates were slightly reduced due to carbon fiber volume fraction reduction. In conclusion, the high glass transition temperature, fracture toughness and CAI behaviour make the green resin matrix composite a potential candidate for aerospace applications.